Acoustic and hearing-perceptual voice analysis in individuals with idiopathic Parkinson's disease in "on" and "off" stages - Santos,Luiza Lara M (2010)
OBJECTIVE: To evaluate the voice quality of patients with idiopathic Parkinson's disease, at the "on" and "off" moments of the disease. METHOD: Five individuals with Parkinson's disease and five of the control group were assessed. All of them underwent the recording of voice and speech. The acoustic parameters analyzed were: fundamental frequency, jitter, shimmer, harmonic noise proportion and index of tremor, besides performing the hearing-perceptual analysis by means of GRBASI scale. The findings were analyzed using statistics through t test and the level of significance adopted was p<0.05. RESULTS: There was no difference in the acoustic parameters in the three analyzed groups. In the hearing-perceptual analysis, patients with idiopathic Parkinson's disease showed altered voice quality and the ones from the control group, neutral vocal quality. CONCLUSION: Patients with idiopathic Parkinson's disease present rough, breathy and unstable vocal quality in both stages. In the acoustic analysis, there are no differences in the studied parameters.